Professional Disease Management Guide for Ornamental Plants - Philip F. Harmon; S. D. Bledsoe (EDIS, 2012)
Florida’s warm, humid environment is a gardener’s paradise and a great location for ornamental plant producers to grow numerous plant species—but these conditions also are suitable for the development of a wide variety of plant pathogens and insects that can spread them. Florida is also a major port of entry for the international trade of ornamental plants, which carries the risk of introducing exotic invasive pathogens, so growers are required to follow certain phytosanitory regulations. These challenges require growers to develop the most efficient production plans possible, incorporating as many tactics as they can to maximize plant health and minimize opportunities for pest and disease outbreaks—a concept known as integrated pest management (IPM). This revised 16-page fact sheet is intended to be used by growers, landscape professionals, and other pest control operators as a reference for managing ornamental plant diseases. Written by P. F. Harmon and S. D. Bledsoe, and published by the UF Department of Plant Pathology, June 2012.